Risk Mitigation of Planning for Procurement of Material Repair and Operation with the Integration of House of Risk and Criticality Ranking Assessment methods based on Failure mode effect Analysis (Case study: PT. Pupuk Iskandar Muda) - Firdaus, Firdaus; Away, Yuwaldi; Huzni, Syifaul (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
To maintain factory reliability, one of the essential factors is the availability of spare parts. Therefore, the spare parts procurement process implemented by the company must be effective and efficient. The complexity of supply chain activities in the spare parts procurement process involving multiple parties and uncertainties that occur in rapid dynamic changes may lead to the emergence of risk events with negative impacts in both short and long terms. The focus of this research is to identify operational risks in the procurement of MRO spare parts and identify alternative efforts to handle the risk of spare parts unavailability. The method used in this research is House of Risk (HOR) to identify risk events, risk agents, and design mitigation action formulations for priority risk agents based on the Aggregate Risk Potential (ARP) value that can suppress the emergence of risk agents. The research results obtained 26 risk events and 25 risk agents. Priority risk agents were obtained based on the highest ARP value, using Pareto analysis approach resulted in 14 risk agents that contributed to 81.32% of the emergence of risk events. There are 9 mitigation actions that can minimize the emergence of risk agents in the supply chain process of MRO spare parts procurement.